Examination of South Carolina's Sex Offender Registration and Notification (SORN) Policy in Reducing Sexual Violence, 1990-2005 - Letourneau, Elizabeth J. ([Verlag nicht ermittelbar], 2015)
This study examined the effects of comprehensive registration and community notification policies on rates of sexual violence in South Carolina. Specifically, it proposed to (1) evaluate whether broad sex offender registration and notification policies have reduced recidivism or deterred new sexual offenses, (2) examine whether unintended effects of broad registration and notification policies occurred, and (3) focus on the effects of registration and notification as it pertained to offenses committed by adults. The study examined whether the introduction of sex offender registration and notification laws in South Carolina were associated with reductions in sexual crimes and, if so, whether this reduction could be attributed to an actual reduction in sexual violence and/or recidivism (i.e., an intended effect) or to changes in criminal judicial processing of individuals for registry crimes (i.e., an unintended effect). Specific study aims included examining whether: (1) South Carolina registration and notification policies had the intended effect of preventing first time sexual offending; (2) South Carolina registration and notification policies had the intended effect of reducing sexual recidivism for known sex offenders; and (3) South Carolina registration and notification policies had the unintended effect of reducing the probability that individuals who committed sexual crimes would be prosecuted or convicted for such crimes. In addition to these primary aims, the researchers also investigated (4) registration violations (e.g., failure to register) were associated with sexual or general recidivism.